Adventure Code Camp: Library Mobile Design in the Backcountry. - Ward, David; Hahn, James; Mestre, Lori (Information Technology & Libraries, 2014)
This article presents a case study exploring the use of a student coding camp as a bottom-up mobile design process to generate library mobile apps. A code camp sources student programmer talent and ideas for designing software services and features. This case study reviews process, outcomes, and next steps in mobile web app coding camps. It concludes by offering implications for services design beyond the local camp presented in this study. By understanding how patrons expect to integrate library services and resources into their use of mobile devices, librarians can better design the user experience for this environment.